2022
DOI: 10.3390/agronomy12092150
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Management of Invasive Fall Armyworm, Spodoptera frugiperda

Abstract: The fall armyworm of maize, Spodoptera frugiperda (J. E. Smith) (Lepidoptera; Noctuidae) is capable of causing a 100% yield loss due to its unforeseen occurrence from the seedling to the cob formation stage. To manage this serious pest, maize growers are tending to apply a high dosage of pesticides. This indiscriminate usage of pesticides has resulted in an unacceptable amount of insect resurgence in maize, harming maize production and consumption. In this review, we prepared a list of practical pest managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 101 publications
1
30
0
Order By: Relevance
“…After three days, the S. frugiperda larvae were collected and weighed in the lab to evaluate mass gain. The caterpillars were then allowed to feed on an artificial diet until they pupated [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After three days, the S. frugiperda larvae were collected and weighed in the lab to evaluate mass gain. The caterpillars were then allowed to feed on an artificial diet until they pupated [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, it has emerged as one of the most important global polyphagous pests of crops [ 20 , 21 ]. FAW is a serious concern in various agroecosystems and can feed on most of the cover and cash crops [ 22 , 23 ]. The management of FAW in recent years has ranged from the use of synthetic pesticides to biopesticides, cultural control, and biological control [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The threats are very significant and therefore the need to limit such damage. The control methods used so far by producers are essentially chemical control with adverse effects on agricultural production itself, health (human and animal) and the environment [17] [18]. Surveys conducted in Ghana in 2018 showed that households sprayed pesticides, including fall armyworm biopesticides up to 12 times, during maize growing seasons [19], which could negatively impact natural enemy populations and increase production costs.…”
Section: Introductionmentioning
confidence: 99%
“…Its larvae feed on at least 353 plant species, including maize (Zea mays L.) and rice (Oryza sativa L.) [18]. Young FAW larvae generally aggregate to feed on leaves of host plants, whereas 3rd-instar and above FAW larvae disperse and consume leaves [19][20]. FAW originated in the tropical-subtropical part of the Western Hemisphere [21].…”
Section: Introductionmentioning
confidence: 99%